PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) DAN RELEVANSINYA DENGAN P5 PADA KELAS IV SEKOLAH DASAR - Dia Ayu Pipit Perpitasari; Tri Sutrisno (STKIP Singkawang, 2025)
The purpose of this study was to describe the implementation of the PjBL model in grade IV of SDN Bakalan 02 and describe its relevance to P5 of the independent curriculum. This study uses a descriptive qualitative approach. Data collection through interview techniques, observation, and documentation. The data obtained were then analyzed with the stages of data collection, data reduction, presentation and drawing conclusions. The results of the study showed that the fourth grade teacher of SDN Bakalan 02 had implemented learning with the PjBL model according to the stages/syntax in the science subject, where students were given a waste recycling project in the form of making a pencil case. This is in line with the theme of a sustainable lifestyle in the P5 dimension and forms six dimensions of the pancasila student profile.